Analisis kesalahan penggunaan ejaan bahasa indonesia pada karangan deskripsi peserta didik kelas iv sekolah dasar - Rohmah Pangestu Suci; Chumdari Chumdari; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2023)
The aims of the study were to find errors in the use of Indonesian spelling that occurred in the descriptive essays of fourth grade elementary school students, to describe the factors causing errors in the use of Indonesian spelling that occurred in students' descriptive essays, and to describe the teacher's efforts to overcome errors in the use of Indonesian spelling that occurred. This research uses a descriptive qualitative method with a case study approach. Data obtained from observation, interviews, and document studies. Errors in writing words are the most common category of errors found and errors in writing absorption elements are the fewest errors made by students. The cause of the error is the lack of students' understanding of the use of spelling. Teachers also have not used strategies or media to support learning to write in their classes. The teacher's effort to overcome these problems is by holding regular composing activities so that students often do writing activities. The teacher also gives direct directions to students when they find errors in students' writing.